Molecular Docking of 6-shogaol and Curcumin on DNMT1 and LSD1 As Potential Agents for Thalassemia Treatment - Joko Setyono; Sekar Cahyo Nurani; Muhamad Salman Fareza; Arif Fadlan; Sarmoko Sarmoko (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Beta-thalassemia therapy is developed by increasing γ-globin production which binds to α-globin to form haemoglobin fetal (HbF). Meanwhile, DNA methyltransferase 1 (DNMT1) and lysine specific demethylase 1 (LSD1) play an important role in silencing the HbF gene by inhibiting the production of HbF and inducing haemoglobin subunit alpha (HbA) expression. 6-Shogaol and curcumin induce HbF by inhibiting signal transducer and activator of transcription 3 (STAT3) expression. Therefore, this study predicts the interaction between 6-shogaol and curcumin on DNMT1 and LSD1. The protein structure of DNMT1 (3SWR) and LSD1 (6KGP) was prepared by removing the water molecules, while the validation step was performed by separating protein from native ligands (sinefungin for 3SWR and flavine-adenine dinucleotide (FAD) for 6KGP) in new protein data bank files. Furthermore, the protein was docked with a native ligand to obtain grid box coordinates, while the root means standard deviation (RMSD) was calculated from the conformation results of the validation process. 6-Shogaol and curcumin were docked with coordinates of the validation results, and the best conformation was visualized with Discovery Studio. The validation step results in the RMSD value of 0.861Å and 1.410Å for DNMT1 and LSD1, respectively. The binding affinity of 6-shogaol and curcumin on DNMT1 was -6.5 kcal/mol and -8.0 kcal/mol, respectively. Furthermore, the binding affinity of 6-shogaol and curcumin on LSD1 was -8.2 kcal/mol and -10.1 kcal/mol, respectively. Amino acid residues found in DNMT1 interaction include Gly1147, Phe1145, Glu1168, Asn1278, Pro1225, Leu1151, Val1580, Ala1579, Asn1578, Trp1170, and Ala1579; meanwhile, Val288, Ser289, Arg310, Gly285, Thr624, Leu659, Lys661, Arg316, Leu625, Tyr761, Trp751, Gly330, and Leu659 were found in LSD1. This study showed that curcumin has the potential to inhibit DNMT1 as well as LSD1 proven by lower bonding energy and stronger bond types compared to sinefungin and FAD native ligands and other DNMT1 and LSD1 inhibitors.